2020
DOI: 10.1681/asn.2020020220
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptome Profiling of the Kidney Glomerulus Identifies Key Cell Types and Reactions to Injury

Abstract: BackgroundThe glomerulus is a specialized capillary bed that is involved in urine production and BP control. Glomerular injury is a major cause of CKD, which is epidemic and without therapeutic options. Single-cell transcriptomics has radically improved our ability to characterize complex organs, such as the kidney. Cells of the glomerulus, however, have been largely underrepresented in previous single-cell kidney studies due to their paucity and intractability.MethodsSingle-cell RNA sequencing comprehensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(151 citation statements)
references
References 51 publications
6
145
0
Order By: Relevance
“…A recent report by Chung et al. 30 suggested that Synpo2 expression may be largely enhanced in smooth muscle cells rather than mesangial cells; however, our findings are consistent with most of the recently published single cell RNA sequencing data 7 ( http://humphreyslab.com/SingleCell ). Furthermore, we confirm that SYNPO2 co-localizes with F-actin and has F-actin bundling activity, and both mutant variants showed decreased actin bundling activity.…”
Section: Discussionsupporting
confidence: 92%
“…A recent report by Chung et al. 30 suggested that Synpo2 expression may be largely enhanced in smooth muscle cells rather than mesangial cells; however, our findings are consistent with most of the recently published single cell RNA sequencing data 7 ( http://humphreyslab.com/SingleCell ). Furthermore, we confirm that SYNPO2 co-localizes with F-actin and has F-actin bundling activity, and both mutant variants showed decreased actin bundling activity.…”
Section: Discussionsupporting
confidence: 92%
“…Single cell sequencing has rapidly enhanced our knowledge of the kidney's expression signature and its cell types (27), thereby helping to uncover the pathophysiology of a variety of conditions including early diabetic nephropathy (28), the composition of a Wilm's tumor (29), and allograft rejection (5). Similar studies in the mouse have facilitated query of murine disease state models (30) and the response to water deprivation (31). In addition, scRNAseq and snRNAseq are foundational technologies for the generation of a kidney cell atlas and detection of novel cell types in the human (2) and the mouse (4,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell sequencing (scRNA-seq) is a technological evolution and provides unprecedented insight into cell communication (10)(11)(12). In experimental studies of renal diseases (13)(14)(15)(16), scRNA-seq technology furthers the understanding of the mechanisms and cell-to-cell interactions involved in disease pathogenesis. In human kidneys (17)(18)(19), scRNA-seq has helped to identify novel cell types, reveal potential mechanisms, and investigate cell communication from distinct aspects.…”
Section: Introductionmentioning
confidence: 99%